The Influence of Enterprise Risk Management Practices on Organizational Performance: Evidence from Kenyan State Corporations - Girangwa, Kakiya Grace; Rono, Lucy; Mose, Jared (Journal of Accounting, Business and Finance Research, 2019)
The main purpose of the study was to determine enterprise risk management effect on organizational performance of state corporations in Kenya. This study was guided by agency theory. The study used explanatory cross sectional survey design. Primary data was collected from structured questionnaires. A survey was carried out on 218 state corporations in Kenya. Data collected was analyzed by use of descriptive and inferential statistics. The research hypotheses were tested using multiple regression analysis. The results revealed that risk structure, governance and process practices had positive and significant effect on organizational performance. This study contributes to theory by centering enterprise risk management on the empirical testing of agency theory on the relationship between enterprise risk management practices and organizational performance. The study recommends that policy makers in state corporations should integrate risk management practices across all functions and business units for the purpose of addressing risks before they even occur.